Penerapan model problem based learning terhadap kemampuan berpikir kritis matematis siswa kelas VIII ditinjau dari kemampuan awal - Mulyawati, Sindi; Fitriani, Nelly; Amelia, Risma (IKIP Siliwangi, 2024)
This research aims to examine the achievement of junior high school students' mathematical critical thinking abilities, both overall and based on students' initial ability categories (low, medium, high). Apart from that, this research wants to compare two learning approaches, namely problem based learning and ordinary learning, towards this achievement. The method used in this research was quasi-experimental by selecting research subjects, namely Class VIII Middle School students consisting of 32 students with low, medium and high KAM classifications. The data collection used is based on test results based on indicators of students' critical mathematical thinking abilities. The results of the research prove that the achievement of critical mathematical thinking abilities of students who learn using the problem-based learning model and the achievements of students who study normally viewed as a whole and based on initial abilities (low, medium, high) have significant differences.